Pengaruh Likuiditas, Ukuran Perusahaan dan Volatilitas Laba Terhadap Leverage Pada Perusahaan Terdaftar di Bursa Efek Indonesia - Habibatul Hidayati; Gina Septiana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
In the business world when Covid 19 hit, the competitive competition between companies weakened. If you want to continue to have an advantage in competitiveness, companies are always required to be able to run company operations efficiently. The company uses retained earnings as a reserve if the company suffers a loss in the future, pays off company debt, increases working capital, and as funds for the company's future expansion. Additional owner's equity participation, along with issuing new shares or selling bonds or bank loans are sources of external funds or funds originating from outside the company itself (Cahyani, 2017). The purpose of this study was to determine the effect of liquidity, company size and earnings volatility on leverage. The sample used is all companies listed on the Indonesia Stock Exchange in 2015-2019 totaling 604 samples. The type of data used is secondary data. The hypotheses in the study were tested using panel data regression. The results showed that liquidity had a negative effect on leverage, while firm size had a positive effect on leverage. On the other hand, earnings volatility has no effect on debt or company leverage.